The novel LAP1: TRF2 complex is associated to DNA damage - Marafona, Ana Marlene Neto (2016)
Lamin associated protein 1 (LAP1) is a type II integral membrane protein located at the inner nuclear membrane (INM). The role of LAP1 remains poorly understand, however, this protein has been associated with several cellular functions due to its interactions with lamins, phosphatase protein 1 (PP1), emerin and torsinA. Moreover, novel putative LAP1 interactors are emerging. A recent study from our group allowed the identification of several novel putative LAP1 interactors involved in telomere signaling and DNA damage responses, namely Ataxia-telangiectasia mutated (ATM), Telomeric repeat binding factor 2 (TRF2), Repressor Activator Protein 1 (RAP1), RAP1 interacting factor 1 homologue (RIF1), Mitotic arrest deficient-like1 (MAD2L1) and Mitotic arrest deficient-like1 binding protein (MAD2L1BP). Protein-protein interactions are crucial in the study of signaling pathways. In this study, TRF2 was identified as a novel LAP1 binding protein using both co-immunoprecipitations and mass spectrometry based methodologies. To determine the functional relevance of the novel complex LAP1:TRF2, HeLa cells were subjected to DNA damage using hydrogen peroxide (H2O2), namely double-stranded breaks (DSBs). In response to DSBs, the expression levels of LAP1 and TRF2 were significantly reduced. The phosphorylation of Histone 2A family member (γ-H2AX) that is considered the hallmark of DSBs was also evaluated. Upon DNA damage, LAP1 not only co-localizes with γ-H2AX in some specific points near nuclear envelope (NE) and nucleus, but also with TRF2 in the nuclear periphery. Moreover, LAP1 and TRF2 have been reported to be crucial for cell cycle progression. Therefore, we decided to pursued this issue. When the NE is reassembled, the complex is located mainly in specific regions of the NE, evidencing that TRF2 allows the attachment of chromosomes to NE membrane in somatic cells. In conclusion, our results are of paramount importance since novel functional insights regarding the novel LAP1:TRF2 complex were achieved particularly related with DNA damage response and cell cycle progression.